Cognitive psychology and instruction - Bruning, Roger H.; Schraw, Gregory J.; Ronning, Royce R. (Upper Saddle River, N.J. : Merrill, 1999)
This text is rooted in a solid base of current cognitive psychology and motivational research and carefully examines how they apply to teaching and learning. It is an appropriate core text for upper-undergraduate or graduate-level courses in cognition/ instruction in education and applied psychology. This edition reflects new developments in the field using a four-part structure which: 1) covers the basic principles of cognitive psychology, 2) examines school-based applications of a cognitive approach, 3) reflects the emphasis on the importance of beliefs in cognition, and 4) describes new approaches to problem solving, critical thinking, and reflective thought.
Includes bibliographical references
Keywords: Learning; Cognitive psychology; Cognitive learning; Instructional systems -- Design